2005
DOI: 10.1177/154405910508400711
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory T-cells Infiltrate Periodontal Disease Tissues

Abstract: CD4+CD25+ regulatory T (Tr) cells are critical in regulating the immune response and thereby play an important role in the defense against infection and control of autoimmune diseases. Our previous studies demonstrated the involvement of autoimmune responses in periodontitis. The aim of this study was to identify CD4+CD25+ Tr cells in periodontitis tissues and compare them with those in gingivitis tissues. Immunohistological analysis of CD4, CD25, and CTLA-4 and the gene expression analysis of FOXP3, TGF-beta1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
145
1
6

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 153 publications
(168 citation statements)
references
References 21 publications
15
145
1
6
Order By: Relevance
“…The elevated number of Treg in periodontitis is in accordance with previous reports suggesting that Treg infiltration could reflect an attempt to control tissue destruction promoted by the chronic inflammatory condition in the gingival tissue via the Th17 response (43)(44)(45)(46). In general, the 15d-PGJ 2 -NC-treated animals showed decreased inflammatory responses, as observed by a significant reduction in the expression of almost all mediators evaluated in the current study (IL-17, IL-6, IL-15, FOXP3, CCL22, IL-10, and TGF-b).…”
Section: Discussionsupporting
confidence: 91%
“…The elevated number of Treg in periodontitis is in accordance with previous reports suggesting that Treg infiltration could reflect an attempt to control tissue destruction promoted by the chronic inflammatory condition in the gingival tissue via the Th17 response (43)(44)(45)(46). In general, the 15d-PGJ 2 -NC-treated animals showed decreased inflammatory responses, as observed by a significant reduction in the expression of almost all mediators evaluated in the current study (IL-17, IL-6, IL-15, FOXP3, CCL22, IL-10, and TGF-b).…”
Section: Discussionsupporting
confidence: 91%
“…19 The regulatory T cells infiltrate gingival tissue in periodontal disease, but lesions with bone resorption show reduced numbers of these cells, increased levels of IL-1␤, and osteoclastogenic RANKL, suggesting that TGF-␤1 signaling is affected in the active disease process. 49,50 Consistent with these findings, loss of TGF-␤1-mediated suppression of T cells results in increased production of osteoclastogenic interferon-␥, TNF-␣, and RANKL, and in bone loss. 51,52 Although a role for keratinocytes in the immunoregulation of periodontal disease has been proposed, the specific functions of cell surface receptors and their ligands, such as ␣v␤6 integrin and TGF-␤1, have not yet been investigated.…”
Section: Discussionsupporting
confidence: 59%
“…21 Ernst et al found that the frequency of forkhead box P3 (FoxP3)/CD25 double-positive cells was strikingly reduced in bone resorption lesions occurring in cases of periodontal disease, with a corresponding increase in RANKL 1 T cells. 22 Kelchtermans et al found that activated CD4 1 CD25 1 Treg cells improve the clinical symptoms of collagen induced arthritis, regulate cytokine production and inhibit osteoclastogenesis both in vitro and in vivo.…”
Section: Modulation Of Treg Cells On Osteoclast Functionsmentioning
confidence: 99%